An integrated systems‐level analysis of the molecular changes resulting from systemic inflammation and amyloid‐beta immunisation in Alzheimer's disease. (20th December 2022) - MacBean, Lachlan Ford; Smith, Adam R.; Smith, Rebecca G.; Boche, Delphine; Lunnon, Katie
Abstract: Background: Post‐mortem histological examination of active amyloid‐beta immunisation participant brains revealed changes to Alzheimer's neuropathology, including high levels of plaque removal and increased microglia phagocytic activity. We hypothesise that there are neuroinflammation‐associated changes to DNA methylation in the post‐mortem brain tissue of the study participants. This study was run in parallel with a study investigating the molecular consequences of systemic infections in AD. As systemic infections are linked to the development and onset of AD; we hypothesise that epigenetic and transcriptomic changes arise in microglia because of systemic inflammation and may drive the progression of AD. Method: PFC and cerebellum tissue was acquired from 16 patients who had received varying doses of the AN‐1792 vaccine or a placebo. PFC tissue was also collected from AD patients who were diagnosed with a systemic infection at time of death (n = 65), AD patients not diagnosed with an infection (n = 70), cognitively normal patients diagnosed with an infection (n = 48). Tissue from cognitively normal patients with no systemic infection diagnosis (n = 66) was also collected, from which age‐matched controls were used for the immunisation study. DNA was extracted from all cases and Infinium methylation EPIC array employed for quantitative interrogation of methylation sites across the genome. Using linear regression analysis, regions of significant differential methylation were identified and annotated to disease relevant genes. Result: Epigenomic analyses have documented differential methylation dynamics in genes previously associated with AD both globally and in glial cells. This study also shows differences in DNA methylation in key genes in systemic infection cases, both in AD and cognitively normal patients, and immunised brain tissue. Conclusion: Discovery of disease‐related methylation dynamics in immunised AD brains indicate a specific regulatory response to amyloid‐beta immunisation. Likewise, differential methylation in immunised and systemic infection cases proposes a role for DNA methylation as a key player in regulating microglial phagocytic activity and suggests key biomarkers as potential therapeutic targets.